KUALITAS PELAYANAN KESEHATAN PASIEN PENERIMA JAMKESMAS DI PUSKESMAS SANGGAU KOTA - Yunita E.21109049, Margareta (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
Quality of Health Care in Patients Recipient Jamkesmas Sanggau City Health Center, includes three aspects studied, including: (a). Attitudes and behavior of workers in providing services. (b). Inhibiting factors in the health center providing good service to the patient, the medical treatment. (c). Efforts made to improve the quality of the health center services to patients on medical treatment. The research found that the attitudes and behavior of workers in providing services are polite and courteous and on time. while the limiting factor in the personnel providing services to users Jamkesmas, including: (a). Health personnel, (b). Drugs, (c). Facilities, and (d). The low level of public education Jamkesmas users. The efforts that have been made in improving the quality of the health center services by providing trainings, courses, refresher training in-service workshops, symposia, and others. Which aims to improve the skills, abilities, and expertise in order to obtain higher labor productivity. In addition, the health center has also sought to improve the quality of healthcare to patients Jamkesmas among other users by providing information about the procedure of administrative services, and the provision of facilities and infrastructure.Keywords: Quality of Service Jamkesmas, Behavioral Services Officer, Obstacles and, EffortService Officers